Eksplorasi Penerapan Pembelajaran IPA Tematik Terpadu dalam Membangun Kesadaran dan Kepedulian Lingkungan Siswa (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
The purpose of this study was to investigate how integrated thematic science teaching can help elementary school students become more aware of and care for the environment. Descriptive qualitative methodology was used, and data were collected through documentation, interviews, and observations. The research findings show how science teaching combined with environmental themes can improve students' conceptual knowledge and foster an environmentally conscious mindset. In addition to understanding environmental issues, students also showed behavioral changes by keeping the school clean, saving water, and encouraging their friends to be responsible for the environment. Active student participation, instructor inventiveness, and school program support are elements that contribute to the success of learning. Meanwhile, time constraints and differences in students' ability levels are the main challenges. As a contextualized character education approach in elementary school, integrated thematic science learning has proven to be successful in shaping the character of environmental stewardship.